Locating Canadian Writing Centres: An Empirical Investigation - Pamela Bromley (Discourse and Writing/Rédactologie, 2017)
As writing centres in Canada face challenges to their existence, funding, and stature, it may be helpful to situate the Canadian experience empirically. This project investigates the number of, geographical, institutional, and physical locations of, and longevity of Canadian writing centres using information from an original database and survey examining writing centres located outside the United States. In the study, findings from Canada are compared to those from the United States, where the only other comprehensive investigations of writing centres have taken place. Results demonstrate that 123 writing centres in Canada are located in all 10 Canadian provinces as well as the Yukon territory, almost half of centres operate under the academic affairs umbrella of their university and are physically located in the library, and that while writing centres in Canada are newer, on average, than their U.S. peers, they may be located in proportionally more universities. Unfortunately, the changes Canadian writing centres are experiencing are not new, as writing centres have previously faced challenges to their existence and place in the university. However, information about the number, institutional and physical location, and longevity of Canadian writing centres may be useful to administrators as they advocate for and further develop their writing centres.